Efficacy and Safety of Adding Sitagliptin in Type 2 Diabetes Patients on Insulin: Age-Stratified Comparison at One Year in the ASSIST-K Study - Takai, Masahiko (J Clin Med Res, 2019)
BACKGROUND: Sitagliptin, the first dipeptidyl peptidase-4 inhibitor, has demonstrated efficacy and safety as monotherapy and as add-on therapy to oral antidiabetic agents or insulin. However, there have been few reports about sitagliptin in elderly patients. The ASSIST-K observational study was performed in patients with type 2 diabetes mellitus (T2DM) receiving sitagliptin as add-on therapy to insulin. Changes of hemoglobin A1c (HbA1c), body weight, and the estimated glomerular filtration rate (eGFR), as well as adverse events, were investigated over 12 months in age-stratified groups. METHODS: Among outpatients with T2DM treated at member institutions of Kanagawa Physicians Association, those starting sitagliptin as add-on therapy to insulin were followed for 12 months. HbA1c (National Glycohemoglobin Standardization Program), body weight, and eGFR were the efficacy endpoints, while adverse events were investigated to assess safety. Patients were stratified into three age groups (≤ 64 years, 65 - 74 years, and ≥ 75 years) for comparison of the endpoints. RESULTS: Among 937 patients on insulin before starting sitagliptin, 821 patients were analyzed after excluding those without HbA1c data at baseline and 12 months. The two groups of elderly patients (65 - 74 years and ≥75 years) had more complications and their HbA1c was lower at initiation of sitagliptin therapy. The dose of sitagliptin, daily number of insulin injections, and number of concomitant oral antidiabetic agents were all lower in the elderly patients. HbA1c showed a significant decrease after initiation of sitagliptin in all age groups, and there were no significant intergroup differences in the change of HbA1c at 12 months. Body weight did not change significantly in any group. eGFR decreased significantly in all groups, with no significant intergroup differences at 12 months. Regarding adverse events, there were no significant intergroup differences in the incidence of severe hypoglycemia, gastrointestinal symptoms, or constipation. CONCLUSIONS: Despite baseline differences in demographic factors and medications, sitagliptin showed good efficacy and safety in all age groups of patients receiving it as add-on therapy to insulin during routine management of T2DM. Adding sitagliptin to insulin achieves similar efficacy and safety outcomes at 12 months in both elderly and non-elderly T2DM patients.